Penyelesaian Sengketa Pembagian Harta Bersama yang Dijadikan Jaminan Hutang Melalui Akta Perdamaian - I Gede Arya Agus Pratama; Ni Luh Mahendrawati; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2020)
Joint assets are assets that a husband and wife can obtain during marriage. Dispute resolution means that the resolution of a conflict between two or more parties originating from different perceptions about an interest or property rights that can have legal consequences for both. The Peace Deed is after the parties mediate, a case agreement is reached on the subject matter of the dispute formulated in the peace agreement. At the appointed hearing, the case filed the peace agreement so that it could be used as a peace deed to resolve their dispute. Based on the explanation above, the following issues will be discussed: 1. Can the joint property of the marriage which is used as a debt security to a third party be the object of a peace agreement by the Plaintiff and Defendant? and 2. How is the process of resolving disputes over joint assets that are used as collateral for debts to third parties? This research uses normative legal research methods, using the statutory approach and conceptual approach, assessing primary and secondary legal materials. The results of this study indicate : That, joint property of a marriage that is in the second place as a debt collateral, cannot be used as an object of ownership disputes, or objects in the peace deed between the plaintiff and the defendant without involving the right holder's collateral, Husband or wife husband and wife disputing shared assets that are used as collateral for debt, must place the collateral holder as one of the cases.